1989
DOI: 10.1099/00221287-135-5-1315
|View full text |Cite
|
Sign up to set email alerts
|

Protoplast Transformation of Bacillus stearothermophilus NUB36 by Plasmid DNA

Abstract: An efficient protoplast transformation system was established for Bacillus stearothermophilus NUB3621 using thermophilic plasmid pTHT15 Tcr (4.5 kb) and mesophilic plasmid pLW05 Cmr (3 kb), a spontaneous deletion derivative of pPL401 Cmr Kmr. The efficiency of transformation of NUB3621 with pLW05 and pTHT15 was 2 x 10(7) to 4 x 10(8) transformants per micrograms DNA. The transformation frequency (transformants per regenerant) was 0.5 to 1.0. Chloramphenicol-resistant and tetracycline-resistant transformants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 38 publications
(33 reference statements)
0
46
0
Order By: Relevance
“…Protoplast transformation involves removing the cell wall (thought to be a barrier to DNA uptake in gram-positive bacteria), DNA uptake, and regeneration of normal walled cells (440). Such techniques were reported in 1984 for heat-treated cells of C. acetobutylicum (390) and in 1989 for B. stearothermophilus (765). Chemically induced competence (e.g., using CaCl 2 or polyethylene glycol) has been widely used for gram-negative bacteria and was also used during the 1980s to develop transformation protocols for Clostridium thermohydrosulfuricum (now Thermoanaerobacter ethanolicus) (634), Streptococcus lactis (591), and Bacillus species (247,662).…”
Section: Native Cellulolytic Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Protoplast transformation involves removing the cell wall (thought to be a barrier to DNA uptake in gram-positive bacteria), DNA uptake, and regeneration of normal walled cells (440). Such techniques were reported in 1984 for heat-treated cells of C. acetobutylicum (390) and in 1989 for B. stearothermophilus (765). Chemically induced competence (e.g., using CaCl 2 or polyethylene glycol) has been widely used for gram-negative bacteria and was also used during the 1980s to develop transformation protocols for Clostridium thermohydrosulfuricum (now Thermoanaerobacter ethanolicus) (634), Streptococcus lactis (591), and Bacillus species (247,662).…”
Section: Native Cellulolytic Strategymentioning
confidence: 99%
“…Chemically induced competence (e.g., using CaCl 2 or polyethylene glycol) has been widely used for gram-negative bacteria and was also used during the 1980s to develop transformation protocols for Clostridium thermohydrosulfuricum (now Thermoanaerobacter ethanolicus) (634), Streptococcus lactis (591), and Bacillus species (247,662). Notwithstanding these reports, transformation of gram-positive bacteria based on protoplasts or chemically induced competence is increasingly viewed as cumbersome, difficult to reproduce, and generally less desirable than electrotransformation (458,765). Conjugation has been used extensively for a few organisms such as C. beijerinckii, as reviewed by Young et al (771), but is not widely used to transform gram-positive bacteria.…”
Section: Native Cellulolytic Strategymentioning
confidence: 99%
“…However, more recent measurements (Nazina et al, 2001) show that the G+C content for G. Group 6B includes NUB3621 (=BGSC 9A5), doubtless the most well-characterized Geobacillus strain from a genetic standpoint. Systems for plasmid transformation (Wu & Welker, 1989), generalized transduction (Welker, 1988) and protoplast fusion (Chen et al, 1986) have been described for this strain, and data generated from those studies have revealed a circular genetic map (Vallier & Welker, 1990). Although the research literature describes NUB3621 as G. stearothermophilus, the recN and 16S rRNA gene sequence analysis presented in Fig.…”
Section: Implications For Geobacillus Taxonomymentioning
confidence: 99%
“…B. stearothermophilus cells were collected by centrifugation and converted to protoplasts (4). The protoplasts were collected by centrifugation (58) Transformation. Protoplasts of B. stearothermophilus were transformed as described by Wu and Welker (58), and transformation of E. coli was accomplished by the procedure described by Perbal (40).…”
Section: Methodsmentioning
confidence: 99%